The Impact of a Defect List and Outstanding List in Expediting the Project Handover Process of PaxOcean’s New Building Centre - Cayitho Calveen veen; Indrastuti (Journal of Civil Engineering and Planning (JCEP), 2023)
At each stage of the construction project, a handover process will be carried out. The handover process in a project is the process of handing over the work results from the contractor to the owner. Before the handover process is carried out, a checking process is carried out on the quality of the project. So it is necessary to make a list of repair work and pending work. The aim of this research is to assess how much influence the use of the defect list method has. This research began with creating a defect list format and an outstanding list format. The data used in this research are the results of observations in the field in the form of problems that arise and work that has not been completed. The results of the research are details of problems that arise on the project and the influence of using the defect list and outstanding list on the project and from making comparisons to the influence of using the method. Accordingly, the results of this research show that there is a positive influence from using the defect list and outstanding list methods.